Implementing theory of planned behavior in health profession education in Ghana - Linda D. Caples (Adult Education Research Conference, 2021)
The process of clinical knowledge translation contributes to clinical decision-making along with interactions with other healthcare professionals, their patients, and the communities they serve. Clinical practice guidelines, patient care experience, and continuing medical education are some of the components that contribute to clinical knowledge translation. The knowledge and interactions help inform a physician’s salient beliefs. Thus, the use of the Theory of Planned Behavior (TPB) facilitates research into how background factors which include knowledge and interactions influence behavioral, normative, and control beliefs and in turn, how those beliefs influence intention and ultimately, physician clinical practice behavior.
Keywords: Theory of planned behavior; Ghana; health profession education; continuing medical education (CME)